Peningkatan Prospek Penjualan Pedagang Sayur Di Pasar Nyanggelan Melalui Pelatihan Marketing Online - Devianti, Amelia; Wardani, Kadek Devi Kalfika Anggria; Gorda, A.A.Ngr.Eddy Supriyadinata (Universitas Muhammadiyah Malang, 2022)
The Covid-19 pandemic has presented a number of challenges for vegetable traders at the Nyanggelan Market, Panjer Village. The existence of regional restrictions has led to a decrease in the number of buyers which has an impact on the decline in the level of sales of vegetable traders at the Nyanggelan Market. To help the vegetable traders of Nyanggelan Village survive in the midst of a crisis, community service activities are carried out by providing online marketing training. supervision or monitoring stage, and evaluation stage. The result of this service activity is the formation of a social media account (instagram)